Global Agricultural Workers from the 17th to the 21st Century - van Nederveen Meerkerk, Elise; Bauer, Rolf (Brill, 2022)
Agricultural workers have long been underrepresented in labour history. This volume aims to change this by bringing together a collection of studies on the largest group of the global work force. The contributions cover the period from the early modern to the present - a period when the emergence and consolidation of capitalism has transformed rural areas all over the globe. Three questions have guided the approach and the structure of this volume. First, how and why have peasant families managed to survive under conditions of advancing commercialisation and industrialisation? Second, why have coercive labour relations been so persistent in the agricultural sector and third, what was the role of states in the recruitment of agricultural workers? Contributors are: Elise van Nederveen Meerkerk, Josef Ehmer, Katherine Jellison, Juan Carmona, James Simpson, Sophie Elpers, Debojyoti Das, Lozaan Khumbah, Karl Heinz Arenz, Leida Fernandez-Prieto, Rachel Kurian, Rafael Marquese, Bruno Gabriel Witzel de Souza, Rogério Naques Faleiros, Alessandro Stanziani, Alexander Keese, Dina Bolokan, and Janina Puder.